2017
DOI: 10.1177/2393861717730621
|View full text |Cite
|
Sign up to set email alerts
|

Representing Women ‘Our Way’: An English Language Teaching Television Programme in Sri Lanka

Abstract: Research on gender representation in English textbooks reveals that messages about gender roles and gender identity transmitted through texts affect the future behaviour of children as they formulate their own roles in society. There is a limited number of studies on visual analysis of gender in textbooks and a dearth of such research on teaching materials in Sri Lanka. This study analyses a TV programme produced to teach school children English in order to uncover the ideological assumptions related to gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The vast majority of roles associated with men are in-command jobs (e.g., doctor and prime minister). It is consistent with the findings of the study by Medawattegedera (2017) who reported that men were more frequently portrayed in in-command jobs. Furthermore, social roles of low status except pilot are associated with women, which implies inferiority of women to men and that women are not capable of carrying out challenging social roles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The vast majority of roles associated with men are in-command jobs (e.g., doctor and prime minister). It is consistent with the findings of the study by Medawattegedera (2017) who reported that men were more frequently portrayed in in-command jobs. Furthermore, social roles of low status except pilot are associated with women, which implies inferiority of women to men and that women are not capable of carrying out challenging social roles.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a nurse associated with women receives commands from a doctor. This result is on par with the study by Medawattegedera (2017) who concluded that subordinate and under-command jobs were associated with women.…”
Section: Discussionsupporting
confidence: 82%
“…Concerning English textbooks in the global contexts, we have surveyed 11 studies about textbooks produced and used in Iran (Foroutan, 2012), Finland (Hjelm et al, 2019), Pakistan (Khan, Sultana, Bughio, & Naz, 2014), Sri Lanka (Medawattegedera, 2017), and Malaysia (Mukundan & Nimehchisalem, 2008). Besides this corpus of work, there are three gender-related studies in English textbooks for global use, namely "New Crown" used in Japan (Clark, 2015), "Oxford English for Careers" (Adel & Enayat, 2016) and "Summit" series (Rashidi & Ghaedsharafi, 2015).…”
Section: Gender Representation In English Textbooksmentioning
confidence: 99%
“…Language textbooks are powerful in directing what a beginning learner attempts to express in the target language and stand up for the learner's cultures (Hjelm et al, 2019). As textbooks bring to bear a strong influence on learners' minds, writers or teachers should address and revise any textbook potential misrepresentations (Medawattegedera, 2017). Hence, how textbooks play a substantial role in fostering learners' critical thinking skills should seriously be considered (Solihati & Hikmat, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, language textbooks may be an extremely successful tool for reshaping students' conceptions of what is and is not acceptable in a specific situation (Curdt-Christiansen, 2017). Moreover, Gender has been discussed and researched in the social sciences, namely education (Medawattegedera, 2018), politics (Baker & Whitehead, 2016;Eum, 2019), sociology (Breckenridge et al, 2019), and linguistics (Beatty Martnez & Dussias, 2019).…”
Section: Introductionmentioning
confidence: 99%